Model Pengembangan Kurikulum Multikultural - Ramdhan , Tri Wahyudi (Al-Insyiroh: Jurnal Studi Keislaman, 2019)
This research discuss about curriculum development of multicultural. The discussions about curriculum development are very diverse which consists of elements (1) planning; (2) implementation (3) evaluation. But in this research, not all elements of curriculum development are a concern, but will only be focused on the curriculum planning element done by SMA 1 Kediri. This research uses a qualitative approach to the type of case study. Whereas in collecting data using participatory observation, in-depth interviews and documentation. And the data collected was analyzed using an interactive analysis model. The results of this research show that curriculum planning in SMA 1 uses a parallel model through three stages, namely (1) strategic planning, (2) program planning and (3) planning of learning activities by producing products containing multicultural dimensions through processes that also contain dimensions multicultural